Complement Verbs in the Bima Language of Tarlawi Sub-Dialect: An Analysis of Forms, Types, and Semantic Functions - M. Aris Akbar; Habiburrahman Habiburrahman (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2026)
The linguistics of smaller communities goes unnoticed in most academic conversations; so does the Bima language, spoken in Bima Regency, West Nusa Tenggara Province, Indonesia. The Bima language belongs to the Central Malayo-Polynesian subgroup of the Austronesian language family and is spoken by approximately one million people in the eastern part of Sumbawa Island. The Bima language has survived through oral tradition and everyday use. However, formal documentation of its grammar remains severely lacking. The Tarlawi sub-dialect of Bima, which is distinct and has not been the focus of study, reflects the above statement, for it can also be considered a unique dialect. The motivation for this study was practical. Upon reviewing the existing literature on regional languages in eastern Indonesia, it was found that even something as basic as Bima grammar, particularly the behavior of verbs, has not been described. This research pays special attention to verbs, as they are more than mere action words; they organize the relationships among various elements in a sentence and often determine whether a sentence is complete. No study on complementation verbs in the predicate of the Tarlawi sub-dialect has been conducted previously. Thus, this study was set out to fill that gap. The researchers collected data through direct fieldwork with native speakers of the Tarlawi subdialect, using a range of naturally occurring language: isolated words, phrases, clauses, full sentences, and connected discourse. Instead of relying on intuition or elicitation alone, the analysis employed deletion and insertion tests. It is a standard yet reliable method for determining if the relevant verb element is obligatory or can be omitted in its grammatical structure. The findings suggest a verbal system that is organized yet adaptable. All verb types in Bima seem to come from a single root verb. This type of verb is derived into intensive verbs, complex transitive verbs, action verbs, process verbs, state verbs, and stative verbs. The relationship to complement verbs varies considerably among the categories – some require a complement verb to form a grammatical sentence, and others can still work without one. In addition to showing the internal grammar of Bima, the research results also constitute the first documentation of complement-verb constructions in the Tarlawi sub-dialect. This contribution hopefully opens the door to further work on this topic and other under-described varieties of Indonesian regional languages.